Role of FGFR3 in Urothelial Carcinoma - Malik Akanksha; Sundaram Sandhya (Iranian Society of Pathology, 2019)
Background and Objective: This study was undertaken to analyze the immunohistochemical expression of fibroblast growth factor receptor (FGFR3) in urothelial carcinoma and correlate its expression with the pathological stage, recurrence and other clinicopathological parameters. Material and Methods: A retrospective study was undertaken on paraffin blocks of 55consecutiveurothelial carcinoma specimens in 28 months received in Sri Ramachandra Medical College, Chennai, India. Blocks with the sections containing the tumor and adjacent normal epithelium were chosen for the immunohistochemical (IHC) study of FGFR3.  Results: IHC expression of FGFR3 in high grade (HG) invasive urothelial carcinoma was positive in 18% cases, 66.7% of HG non-invasive urothelial and 82.6% of low grade (LG) non-invasive urothelial carcinomas. The FGFR3 expression was presented in 78.1% of non-invasive carcinoma. In case of invasive urothelial carcinoma, the FGFR3 positivity was observed in 18.2% of tumors (P<0.05). FGFR3 expression in LG tumors was positive in 82.6 % of the cases whereas 32.3% of HG cases were positive for FGFR3 (P<0.05). FGFR3 was expressed in 14.3 % of HG invasive tumors which recurred. HG non-invasive tumors were positive for FGFR3 in 80% of the cases. LG non-invasive tumors were positive for FGFR3 in 72.7% of cases (P<0.05). Conclusion: The expression of FGFR3 is higher in low grade, non-invasive tumors and recurrent non-invasive tumors. The targeted therapy for FGFR3 may be used as one of the modes of treatment for urothelial carcinoma. It can also be used as a marker to determine the grade in difficult cases and the risk of recurrence.